2008
DOI: 10.1152/ajplung.00134.2007
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic upregulates MMP-9 and inhibits wound repair in human airway epithelial cells

Abstract: As part of the innate immune defense, the polarized conducting lung epithelium acts as a barrier to keep particulates carried in respiration from underlying tissue. Arsenic is a metalloid toxicant that can affect the lung via inhalation or ingestion. We have recently shown that chronic exposure of mice or humans to arsenic (10-50 ppb) in drinking water alters bronchiolar lavage or sputum proteins consistent with reduced epithelial cell migration and wound repair in the airway. In this report, we used an in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 50 publications
5
56
0
Order By: Relevance
“…Animal studies showed tissue inflammation and increased morphologic changes in the lung with increasing arsenic exposure (31,35). Impaired repair mechanisms in the human epithelium of the airway have also been demonstrated by the up-regulation of metalloproteinase-9 in extracellular matrix in arsenic-exposed subjects (36). Clara cell 16 protein, which is known to play an important role in protecting the alveolar epithelium of the lung in chronic inflammation (37,38), has also been impacted by arsenic exposure (27).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies showed tissue inflammation and increased morphologic changes in the lung with increasing arsenic exposure (31,35). Impaired repair mechanisms in the human epithelium of the airway have also been demonstrated by the up-regulation of metalloproteinase-9 in extracellular matrix in arsenic-exposed subjects (36). Clara cell 16 protein, which is known to play an important role in protecting the alveolar epithelium of the lung in chronic inflammation (37,38), has also been impacted by arsenic exposure (27).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 has also been shown to stimulate the repair of bronchial epithelial cells in vitro (94), and MMP-9-mediated stimulation of HBE cell migration was shown to be dependent on the activation of dual oxidase 1 (Duox1) (184). In contrast, exposure of 16HBE14o-to arsenic caused increased MMP-9 activity and expression and decreased cell migration, whereas inhibition of MMP-9 enhanced wound repair (113). Another group previously found that plasminogen activator inhibitor-1 (PAI-1), another protein associated with matrix degradation, decreased the repair of ATII cells by binding to vitronectin (89).…”
Section: Matrix Integrins and Glycoproteinsmentioning
confidence: 99%
“…This chapter specifically addresses the mechanisms implicated in the carcinogenic and neurotoxic effects of arsenic. Further effects such as those on cutaneous and systemic immunity (Biswas et al, 2008;Olsen et al, 2008;Liao et al, 2009b;Raqib et al, 2009), on developmental and reproductive toxicity and on endocrine processes including estrogen receptor mediated signalling (Watson and Yager, 2007) are partly addressed in the respective sections but are not addressed in detail here.…”
Section: Molecular Mechanismsmentioning
confidence: 99%